Unusual B-Lymphoid Blastic Crisis as Initial Presentation of Chronic Myeloid Leukemia Imposes Diagnostic Challenges - Momen, Nouran; Baysal, Bora; Jani Sait, Sheila; Tario, Joseph; Qian, You-Wen (Case Reports in Hematology, 2022)
Chronic myeloid leukemia (CML) is a clonal hematopoietic stem cell disorder, characterized by reciprocal translocation t(9,22) (q34; q11), leading to increased myeloid proliferation. Most cases are diagnosed in the chronic phase (CP). However, a minority of cases can be present in the blastic phase (BP). In most patients with CML-BP, the blasts have a myeloid phenotype, however, in 20–30% of cases, the blasts have a lymphoid phenotype, mostly a B-cell phenotype. It is challenging to differentiate CML B-lymphoblastic phase (CML-BLP) from Ph + primary B-acute lymphoblastic leukemia (B-ALL) especially when the CML-BLP is the initial presentation of the disease, which is uncommon. We report here an unusual case of CML-BLP as an initial presentation of the disease without typical CML morphological findings. This case demonstrates diagnostic challenges and emphasizes the importance of an integrated approach using morphology, multiparametric flow cytometry, cytogenetic studies, and molecular studies to render an accurate diagnosis.